Pelatihan Pembuatan Baju Kaos: Peningkatan Kualitas Produk dan Daya Saing UMKM D’limalima Cileungsi, Kabupaten Bogor - Djonaedi, Emmidia; Rachmah Nanda Kartika; Endang Yuniarti; Hb. Rudi Kusumantoro; Yoga Putra Pratama; Moch Yana Hardiman (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
Convection is a mass production business, and this production scale is on the small industry scale. D'LimaLima small industry is a screen printing start-up small industry that was only founded in 2023. This small industry is interested in starting a T-shirt screen printing business in various sizes. This activity was carried out by providing training in making t-shirts for 1 day. Participants who are beginners have different learning times for each person and each type of machine. The training methods that will be used include: Lecture, discussion, practice. From the observations, it was concluded that for all participants as beginners, sewing one t-shirt took more than one hour. This is caused by the lack of skills in using the three types of sewing machines (overlock, chain, double stitch). It took the three sewing trainers less than 1 hour to make one t-shirt, because they were trained and used to using industrial type sewing machines like that. On average, participants needed 10 minutes and 5 re-stitches when sewing on patchwork. so it can be confirmed that participants also need to repeat the activity more than five times to become more skilled at using the machine